Clinical characteristics of asthmatic children with Vitamin D deficiency at Jordan University Hospital: A retrospective study - Al-Zayadneh, Enas; Al-Bitar, Malak; Al-Ani, Abdallah; Saadeh, Aseel; Al-Oqaily, Wafi; Yameen, Abdel-Rahman; Al Shamasneh, Mohammad; AL-Iede, Montaha (Jordan Medical Journal, 2021)
Objective: Bronchial asthma is the most common chronic condition in the pediatric population around the world. Increasing evidence suggests an association between Vitamin D deficiency and asthma. This study aims to evaluate the prevalence of vitamin D deficiency in children with bronchial asthma in Jordan University Hospital, investigate the clinical characteristics of the study population, and examine the correlation between vitamin D levels and asthma severity and control. Methodology: A retrospective chart review was conducted on 201 asthmatic children, aged 1 to 18 years, who received medical care at Jordan University Hospital from 2015 to 2018. Vitamin D levels were recorded for all study populations. Patient demographic and clinical characteristics such as body mass index, feeding status, pulmonary function test, and pediatric intensive care admissions were collected. Demographic and clinical characteristics were compared among three categories of vitamin D levels, and a correlation between asthma severity and vitamin D level was assessed. Results: Out of 201 participants included in the study, 51.7% were vitamin D deficient, 26.6% were vitamin D insufficient, and 21.6% were vitamin D sufficient. The following variables had significant correlations with vitamin D levels; frequency of inhaled Salbutamol usage (p=.028), PICU admissions (p=.011), feeding status at six months (p=.039), and the number of admissions per year (p=.028).Conclusion: Vitamin D deficiency is prevalent in asthmatic children and correlates with the severity and control of asthma in our target population. Health care providers of asthmatic children are encouraged by our results to assess vitamin D levels in these patients.